If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -2(x + -5) = 0 Reorder the terms: 16 + -2(-5 + x) = 0 16 + (-5 * -2 + x * -2) = 0 16 + (10 + -2x) = 0 Combine like terms: 16 + 10 = 26 26 + -2x = 0 Solving 26 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + -2x = 0 + -26 Combine like terms: 26 + -26 = 0 0 + -2x = 0 + -26 -2x = 0 + -26 Combine like terms: 0 + -26 = -26 -2x = -26 Divide each side by '-2'. x = 13 Simplifying x = 13
| -21x+5=-40 | | 11x+13=108 | | half(7x-2)+5=2x+7 | | 3a^2-8a+4=0 | | 3x+8=2x+1 | | 8x-5=8(x+6) | | -7n-3(n+7)=3-6n | | -72-3(n+7)=3-6n | | 7+(-3)v=6+v | | y=hx+f | | 3x^3+14x^2-12x=0 | | 9c+5-6=9 | | 5x^3-3x-2=0 | | 16x=12x+52 | | X-1=2y | | a^3b^5x=a^7b^5c^3 | | 3y^5*6y= | | 12x(x+1)=42(x+1)-(3x-42) | | 4.5=-3(-2.5)+b | | 2n-14=-8(7+5n) | | 2n-1=-8(7+5n) | | 3.14r^2=5 | | 3(3.5x+3.75)=3(4.75x+4) | | 6x-2=3x-44 | | 9e-5=22 | | 6x-1=2x-93 | | 25X^2+8X=0 | | 60=5x-5 | | 7(4x-9)+10=5x-5 | | 9x-4=75 | | -15x=1479 | | 9-7x=209-42x |